2021
DOI: 10.1590/1807-1929/agriambi.v25n12p833-839
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of cations in lettuce cultivars under low-cost hydroponic system with brackish waters

Abstract: The use of brackish water to cultivate lettuce can cause nutritional imbalances, impairing production. In this context, the objective of the present study was to evaluate the effect of salinity on the accumulation of dry matter of the aerial part and macronutrients K, Ca and Mg and their relations with Na in lettuce cultivars grown in a low-cost hydroponic system. The experiment was conducted in a randomized block design, in a 6 × 2 factorial scheme, with four replicates. The treatments consisted of six electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These results are in accordance with the studies carried out by Muchecua et al (2022) working with parsley crop under salt stress. Other authors (Soares et al, 2016;Silva et al, 2021a) also observed a reduction in Mg 2+ uptake under salt stress conditions.…”
Section: Magnesiummentioning
confidence: 74%
See 2 more Smart Citations
“…These results are in accordance with the studies carried out by Muchecua et al (2022) working with parsley crop under salt stress. Other authors (Soares et al, 2016;Silva et al, 2021a) also observed a reduction in Mg 2+ uptake under salt stress conditions.…”
Section: Magnesiummentioning
confidence: 74%
“…Other authors, studying some leafy plants in hydroponic system, also Mineral nutrition and hydroponic kale production under saline stress and calcium nitrate verified a reduction in calcium contents in response to salt stress, such as lettuce (Silva et al, 2021a) and parsley (Muchecua et al, 2022). The increase of calcium contents in S3 can be explained by a greater availability of Ca 2+ in the nutrient solution, increasing an availability of this nutrient and favoring its uptake to the detriment of Na + uptake, since this nutrient shows antagonistic interaction (Marschner, 2012).…”
Section: Calciummentioning
confidence: 89%
See 1 more Smart Citation